Improving PFAS Rejection by Ultrafiltration Membranes via Polyelectrolyte Multilayer Coating - Turk, Oruc Kaan; Cakmakci, Mehmet; Zengin, Ismail Hakki; Karadag, Dogan; Yuksel, Ebubekir (MDPI, 2025)
Per- and polyfluoroalkyl substances (PFASs), used since the 1940s, are persistent and carcinogenic pollutants. Water is a major exposure route; effective removal is essential. While nanofiltration (NF) and reverse osmosis (RO) are effective but costly, ultrafiltration (UF) membranes offer advantages such as lower cost and higher flux, but their relatively large pore size makes them ineffective for PFAS compounds like perfluorooctane sulfonic acid (PFOS) and perfluorooctanoic acid (PFOA). Since PFAS removal depends on both pore size and surface properties, this study investigates the effect of polyelectrolyte multilayer coatings using poly(allylamine hydrochloride) (PAH) and poly(acrylic acid) (PAA) on the zeta potential of UF membranes. Pristine UF membranes showed limited performance (UP150: similar to 2% for both PFOS and PFOA; UP020: 34.4% PFOS, 24.1% PFOA), while coating significantly enhanced removal (coated UP150: 45.3% PFOS, 43.4% PFOA; coated UP020: 77.8% PFOS, 73.3% PFOA). The modified UF membranes achieved PFAS removal efficiencies significantly closer to NF membranes, though still below those of RO (e.g., BW30XLE: up to 91.0% PFOS, 88.3% PFOA; NP030: up to 81.0% PFOS, 79.3% PFOA). Findings emphasize the importance of membrane surface charge and suggest that modified UF membranes offer a promising, low-cost alternative for PFAS removal under low-pressure conditions.
Keywords: PFOA; PFOS; PFAS; membrane technology; zeta potential; PERFLUOROOCTANE SULFONATE; WATER; SUBSTANCES; REMOVAL; TECHNOLOGIES; NANOREACTORS; Biochemistry & Molecular Biology; Chemistry; Engineering; Materials Science; Polymer Science